From face-to-face to screen-to-screen: exploring the multifaceted dimensions of digital mental health care - Maqsood, Aneela; Gul, Seema; Zahra, Touseef; Noureen, Nazia; Khattak, Amira (Frontiers in Psychiatry, 2024)
Background With the onset of the COVID-19 pandemic, the world witnessed an unprecedented surge in the adoption of digital platforms across various sectors, including mental health care. In countries such as Pakistan, where traditional face-to-face therapy practices hold social and cultural significance, transitioning to digital therapeutic methods presents a range of unique opportunities and challenges. Objectives This research aimed to explore the dynamics, implications, and perceptions surrounding digital therapeutic care within the Pakistani sociocultural context. Given the paucity of literature on this subject in the Pakistani context, this study aims to bridge the evidence gap between trends in digital therapy and localized practices. The main goal was to understand the benefits, issues, and challenges therapists and clients face when adopting digital modes for therapeutic care. Method For this study, primary data was gathered from counsellors and therapists using a qualitative in-depth interview guide. Using a thematic analysis approach, key themes were derived from the interviews that provided insights into the experiences and perceptions of the participants. Results The study revealed that digital platforms have great potential in breaking down geographical barriers making therapeutic interventions more accessible to a wider demographic. This increased accessibility also brought about a level of comfort for clients as they could access therapy from their familiar surroundings. Among the challenges that needed attention, security and confidentiality stood out, requiring strict measures to safeguard client’s data. The shift also brought to light the diverse range of feedback from clients, which was influenced by factors like age and technological proficiency. Moreover, the digital transition posed challenges for both therapists and clients, with many facing an adjustment period as they transitioned from face-to-face to online sessions. One significant challenge was the perceived difficulty in fostering a deep interpersonal connection in a virtual environment. This was further compounded by the need for therapists to modify traditional therapeutic techniques to fit the online mode. Conclusion and implications The study underscores the evolving nature of digital therapy in Pakistan, setting a foundation for further exploration in aligning technology with therapeutic needs, ensuring optimal benefits for clients while preserving the sanctity and efficacy of the therapeutic relationship.